Effect of intrahippocampal microinjection of VU0155041, a positive allosteric modulator of mGluR4, on long term potentiation in a valproic acid-induced autistic male rat model - Ebrahimi, Zahra; Gholipour, Parsa; Mohammadkhani, Reihaneh; Ghahremani, Reza; Sarihi, Abdolrahman; Komaki, Alireza; Salehi, Iraj; Karimi, Seyed Asaad (IBRO neuroscience reports, 2024)
The precise cause of autism spectrum disorder (ASD) is not fully understood. Despite the involvement of glutamatergic dysregulation in autism, the specific contribution of mGlu4 receptors to synaptic plasticity remains unclear. Using the positive allosteric modulator VU0155041, we aimed to restore long-term potentiation (LTP) in the perforant path-dentate gyrus (PP-DG) pathway in VPA-induced autistic rat model. High-frequency stimulation was applied to the PP-DG synapse to induce LTP, while the VU0155041 was administered into the DG. Unexpectedly, VU0155041 failed to alleviate the observed LTP reduction in VPA-exposed rats, further resulting in a significant decrease in population spike LTP. This unexpected outcome prompts discussion on the complex nature of mGlu4 receptor modulation, highlighting potential interference with physiological processes underlying synaptic plasticity.